Strategies for Scaling Tested and Effective Family-Focused Preventive Interventions to Promote Children's Cognitive, Affective, and Behavioral Health: Workshop in Brief - Institute of Medicine; National Research Council (The National Academies Press, 2015)
On April 1-2, 2014, the Board on Children, Youth, and Families of the Institute of Medicine and the National Research Council held a 2-day workshop to discuss the successes and challenges of scaling family-focused interventions. A range of settings involved in preventive family-focused interventions were highlighted, including primary care settings, schools, homes, and on the Web. Collectively this knowledge will be used to explore new and innovative ways to broaden the reach of effective programs and to generate alternative paradigms for strengthening families. This brief summary of the workshop highlights topics raised by presenters and participants.
Keywords: Health and Medicine; Behavioral and Social Sciences

Strategies for Scaling Effective Family-Focused Preventive Interventions to Promote Children's Cognitive, Affective, and Behavioral Health: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2014)
Over the last three decades, researchers have made remarkable progress in creating and testing family-focused programs aimed at fostering the cognitive, affective, and behavioral health of children. These programs include universal interventions, such as those for expecting or new parents, and workshops for families whose children are entering adolescence, as well as programs targeted to especially challenged parents, such as low-income single teens about to have their first babies, or the parents of children with autism. Some family-focused programs have been shown to foster significantly better outcomes in children, including enhanced educational performance, and reduced rates of teen pregnancy, substance abuse, and child conduct and delinquency, as well as reduced child abuse. The favorable cost-benefit ratios of some of these programs are due, in part, to the multiple and far-ranging effects that family-focused prevention programs targeting children can have. Other family-focused programs have shown success in smaller academic studies but have not been widely applied, or have not worked as effectively or failed when applied to more diverse real-world settings. Strategies for Scaling Effective Family-Focused Preventive Interventions to Promote Children's Cognitive, Affective, and Behavioral Health is the summary of a workshop convened by the Institute of Medicine Forum on Promoting Children's Cognitive, Affective, and Behavioral Health to explore effective preventive interventions for youth that can modify risk and promote protective factors that are linked to mental, emotional, and behavioral health, and how to apply this existing knowledge. Based on the 2009 report Preventing Mental, Emotional, and Behavioral Disorders Among Young People, this report considers how to build a stronger research and practice base around the development and implementation of programs, practices, and policies that foster children's health and well-being across the country, while engaging multi-sectorial stakeholders. While research has advanced understanding of risk, promotive, and protective factors in families that influence the health and well-being of youth, a challenge remains to provide family-focused interventions across child and adolescent development at sufficient scale and reach to significantly reduce the incidence and prevalence of negative cognitive, affective, and behavioral outcomes in children and adolescents nationwide, as well as to develop widespread demand for effective programs by end users. This report explores new and innovative ways to broaden the reach and demand for effective programs and to generate alternative paradigms for strengthening families.
Keywords: Health and Medicine; Behavioral and Social Sciences

Families Caring for an Aging America - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Family caregiving affects millions of Americans every day, in all walks of life. At least 17.7 million individuals in the United States are caregivers of an older adult with a health or functional limitation. The nation's family caregivers provide the lion's share of long-term care for our older adult population. They are also central to older adults' access to and receipt of health care and community-based social services. Yet the need to recognize and support caregivers is among the least appreciated challenges facing the aging U.S. population. Families Caring for an Aging America examines the prevalence and nature of family caregiving of older adults and the available evidence on the effectiveness of programs, supports, and other interventions designed to support family caregivers. This report also assesses and recommends policies to address the needs of family caregivers and to minimize the barriers that they encounter in trying to meet the needs of older adults.
Keywords: Health and Medicine

Achieving Behavioral Health Equity for Children, Families, and Communities: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
In November 2017, the The Forum on Promoting Children's Cognitive, Affective, and Behavioral Health, in collaboration with the Roundtable on the Promotion of Health Equity, convened a workshop on promoting children's behavioral health equity. The workshop used a socio-ecological developmental model to explore health equity of children and families, including those with complex needs and chronic conditions. Particular attention was paid to challenges experienced by children and families in both rural and urban contexts, to include but not limited to poverty, individual and institutional racism, low-resourced communities, and hindered access to educational and health care services. Workshop participants also engaged in solution-oriented discussions of initiatives, policies, and programs that aim to improve social determinants of health, opportunities for behavioral health promotion, and access to quality services that address the behavioral health of all children and families. This publication summarizes the presentations and discussion of the event.
Keywords: Health and Medicine; Behavioral and Social Sciences

Health and Behavior: The Interplay of Biological, Behavioral, and Societal Influences - Institute of Medicine (The National Academies Press, 2001)
Health and Behavior reviews our improved understanding of the complex interplay among biological, psychological, and social influences and explores findings suggested by recent research—including interventions at multiple levels that we can employ to improve human health. The book covers three main areas: What do biological, behavioral, and social sciences contribute to our understanding of health—including cardiovascular, immune system and brain functioning, behaviors that influence health, the role of social networks and socioeconomic status, and more. What can we learn from applied research on interventions to improve the health of individuals, families, communities, organizations, and larger populations? How can we expeditiously translate research findings into application?
Keywords: Health and Medicine

Preventing Mental, Emotional, and Behavioral Disorders Among Young People: Progress and Possibilities - National Research Council; Institute of Medicine (The National Academies Press, 2009)
Mental health and substance use disorders among children, youth, and young adults are major threats to the health and well-being of younger populations which often carryover into adulthood. The costs of treatment for mental health and addictive disorders, which create an enormous burden on the affected individuals, their families, and society, have stimulated increasing interest in prevention practices that can impede the onset or reduce the severity of the disorders. Prevention practices have emerged in a variety of settings, including programs for selected at-risk populations (such as children and youth in the child welfare system), school-based interventions, interventions in primary care settings, and community services designed to address a broad array of mental health needs and populations. Preventing Mental, Emotional, and Behavioral Disorders Among Young People updates a 1994 Institute of Medicine book, Reducing Risks for Mental Disorders, focusing special attention on the research base and program experience with younger populations that have emerged since that time. Researchers, such as those involved in prevention science, mental health, education, substance abuse, juvenile justice, health, child and youth development, as well as policy makers involved in state and local mental health, substance abuse, welfare, education, and justice will depend on this updated information on the status of research and suggested directions for the field of mental health and prevention of disorders.
Keywords: Health and Medicine; Behavioral and Social Sciences

Fetal Alcohol Syndrome: Diagnosis, Epidemiology, Prevention, and Treatment - Institute of Medicine (The National Academies Press, 1996)
It sounds simple: Women who drink while pregnant may give birth to children with defects, so women should not drink during pregnancy. Yet in the 20 years since it was first described in the medical literature, fetal alcohol syndrome (FAS) has proved to be a stubborn problem, with consequences as serious as those of the more widely publicized "crack babies." This volume discusses FAS and other possibly alcohol-related effects from two broad perspectives: diagnosis and surveillance, and prevention and treatment. In addition, it includes several real-life vignettes of FAS children. The committee examines fundamental concepts for setting diagnostic criteria in general, reviews and updates the diagnostic criteria for FAS and related conditions, and explores current research findings and problems associated with FAS epidemiology and surveillance. In addition, the book describes an integrated multidisciplinary approach to research on the prevention and treatment of FAS. The committee: Discusses levels of preventive intervention. Reviews available data about women and alcohol abuse and treatment among pregnant women. Explores the psychological and behavioral consequences of FAS at different ages. Examines the current state of knowledge about medical and therapeutic interventions, education efforts, and family support programs. This volume will be of special interest to physicians, nurses, mental health practitioners, school and public health officials, policymakers, researchers, educators, and anyone else involved in serving families and children, especially in high risk populations.
Keywords: Health and Medicine

Violence in Families: Assessing Prevention and Treatment Programs - Rosemary Chalk; Patricia A. King (The National Academies Press, 1998)
Reports of mistreated children, domestic violence, and abuse of elderly persons continue to strain the capacity of police, courts, social services agencies, and medical centers. At the same time, myriad treatment and prevention programs are providing services to victims and offenders. Although limited research knowledge exists regarding the effectiveness of these programs, such information is often scattered, inaccessible, and difficult to obtain. Violence in Families takes the first hard look at the successes and failures of family violence interventions. It offers recommendations to guide services, programs, policy, and research on victim support and assistance, treatments and penalties for offenders, and law enforcement. Included is an analysis of more than 100 evaluation studies on the outcomes of different kinds of programs and services. Violence in Families provides the most comprehensive review on the topic to date. It explores the scope and complexity of family violence, including identification of the multiple types of victims and offenders, who require different approaches to intervention. The book outlines new strategies that offer promising approaches for service providers and researchers and for improving the evaluation of prevention and treatment services. Violence in Families discusses issues that underlie all types of family violence, such as the tension between family support and the protection of children, risk factors that contribute to violent behavior in families, and the balance between family privacy and community interventions. The core of the book is a research-based review of interventions used in three institutional sectors—social services, health, and law enforcement settings—and how to measure their effectiveness in combating maltreatment of children, domestic violence, and abuse of the elderly. Among the questions explored by the committee: Does the child protective services system work? Does the threat of arrest deter batterers? The volume discusses the strength of the evidence and highlights emerging links among interventions in different institutional settings. Thorough, readable, and well organized, Violence in Families synthesizes what is known and outlines what needs to be discovered. This volume will be of great interest to policymakers, social services providers, health care professionals, police and court officials, victim advocates, researchers, and concerned individuals.
Keywords: Behavioral and Social Sciences; Health and Medicine

Behavioral Science and the Secret Service: Toward the Prevention of Assassination - Institute of Medicine (The National Academies Press, 1981)
Keywords: Health and Medicine

Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Considerations for the Design of a Systematic Review of Care Interventions for Individuals with Dementia and Their Caregivers: Letter Report provides input into the design of an Agency for Healthcare Research and Quality (AHRQ) systematic review of evidence on effective care-related interventions for people with dementia and their caregivers. This letter report describes potential changes and considerations for the key questions and study design that would result in the most informative and timely evidence review on this topic.
Keywords: Health and Medicine

Pathways of Addiction: Opportunities in Drug Abuse Research - Institute of Medicine (The National Academies Press, 1996)
Drug abuse persists as one of the most costly and contentious problems on the nation's agenda. Pathways of Addiction meets the need for a clear and thoughtful national research agenda that will yield the greatest benefit from today's limited resources. The committee makes its recommendations within the public health framework and incorporates diverse fields of inquiry and a range of policy positions. It examines both the demand and supply aspects of drug abuse. Pathways of Addiction offers a fact-filled, highly readable examination of drug abuse issues in the United States, describing findings and outlining research needs in the areas of behavioral and neurobiological foundations of drug abuse. The book covers the epidemiology and etiology of drug abuse and discusses several of its most troubling health and social consequences, including HIV, violence, and harm to children. Pathways of Addiction looks at the efficacy of different prevention interventions and the many advances that have been made in treatment research in the past 20 years. The book also examines drug treatment in the criminal justice setting and the effectiveness of drug treatment under managed care. The committee advocates systematic study of the laws by which the nation attempts to control drug use and identifies the research questions most germane to public policy. Pathways of Addiction provides a strategic outline for wise investment of the nation's research resources in drug abuse. This comprehensive and accessible volume will have widespread relevance—to policymakers, researchers, research administrators, foundation decisionmakers, healthcare professionals, faculty and students, and concerned individuals.
Keywords: Health and Medicine

Through the Kaleidoscope: Viewing the Contributions of the Behavioral and Social Sciences to Health -- The Barbara and Jerome Grossman Symposium - Institute of Medicine; National Research Council (The National Academies Press, 2002)
The importance of behavioral, social, economic, and environmental influences on health is increasingly recognized. Further, the relationships among genetic factors, social influences, and the physical environment are now of growing interest to the research, policy, public health, and clinical communities. As research in these areas yields new knowledge about these interactions, we are faced with the challenge of applying and translating that knowledge into practical applications or policy directions.To advance this challenge, the Institute of Medicine (IOM) brought together experts and collaborators at a symposium in May 2001. The symposium featured five reports released in the last 12 months by the IOM and the Division of Behavioral and Social Sciences and Education (DBASSE). The reports were the starting point for assessing the status of behavioral and social science research relating to health, identifying where the greatest opportunities appear to lie in translating this research into clinical medicine, public health, and social policy; and recognizing the barriers that continue to impede significant progress in conducting and utilizing this field of research. This report is a proceedings of the symposium from these experts in the field. Topics covered include research design, training, infrastructure investments, grant making, etiology, interventions, and priority investments necessary to support rapid advances in the behavioral and social sciences.
Keywords: Health and Medicine

Progress in Preventing Childhood Obesity: How Do We Measure Up? - Institute of Medicine (The National Academies Press, 2007)
The remarkable increase in the prevalence of obesity among children and youth in the United States over a relatively short timespan represents one of the defining public health challenges of the 21st century. The country is beginning to recognize childhood obesity as a major public health epidemic that will incur substantial costs to the nation. However, the current level of investment by the public and private sectors still does not match the extent of the problem. There is a substantial underinvestment of resources to adequately address the scope of this obesity crisis. At this early phase in addressing the epidemic, actions have begun on a number of levels to improve the dietary patterns and to increase the physical activity levels of young people. Schools, corporations, youth-related organizations, families, communities, foundations, and government agencies are working to implement a variety of policy changes, new programs, and other interventions. These efforts, however, generally remain fragmented and small in scale. Moreover, the lack of systematic monitoring and evaluation of interventions have hindered the development of an evidence base to identify, apply, and disseminate lessons learned and to support promising efforts to prevent childhood obesity. Progress in Preventing Childhood Obesity: How Do We Measure Up? examines the progress made by obesity prevention initiatives in the United States from 2004 to 2006. This book emphasizes a call to action for key stakeholders and sectors to commit to and demonstrate leadership in childhood obesity prevention, evaluates all policies and programs, monitors their progress, and encourages stakeholders to widely disseminate promising practices. This book will be of interest to federal, state, and local government agencies; educators and schools; public health and health care professionals; private-sector companies and industry trade groups; media; parents; and those involved in implementing community-based programs and consumer advocacy.
Keywords: Health and Medicine

Contagion of Violence: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2013)
The past 25 years have seen a major paradigm shift in the field of violence prevention, from the assumption that violence is inevitable to the recognition that violence is preventable. Part of this shift has occurred in thinking about why violence occurs, and where intervention points might lie. In exploring the occurrence of violence, researchers have recognized the tendency for violent acts to cluster, to spread from place to place, and to mutate from one type to another. Furthermore, violent acts are often preceded or followed by other violent acts. In the field of public health, such a process has also been seen in the infectious disease model, in which an agent or vector initiates a specific biological pathway leading to symptoms of disease and infectivity. The agent transmits from individual to individual, and levels of the disease in the population above the baseline constitute an epidemic. Although violence does not have a readily observable biological agent as an initiator, it can follow similar epidemiological pathways. On April 30-May 1, 2012, the Institute of Medicine (IOM) Forum on Global Violence Prevention convened a workshop to explore the contagious nature of violence. Part of the Forum's mandate is to engage in multisectoral, multidirectional dialogue that explores crosscutting, evidence-based approaches to violence prevention, and the Forum has convened four workshops to this point exploring various elements of violence prevention. The workshops are designed to examine such approaches from multiple perspectives and at multiple levels of society. In particular, the workshop on the contagion of violence focused on exploring the epidemiology of the contagion, describing possible processes and mechanisms by which violence is transmitted, examining how contextual factors mitigate or exacerbate the issue. Contagion of Violence: Workshop Summary covers the major topics that arose during the 2-day workshop. It is organized by important elements of the infectious disease model so as to present the contagion of violence in a larger context and in a more compelling and comprehensive way.
Keywords: Health and Medicine

Promoting Health: Intervention Strategies from Social and Behavioral Research - Institute of Medicine (The National Academies Press, 2000)
At the dawn of the twenty-first century, Americans enjoyed better overall health than at any other time in the nation's history. Rapid advancements in medical technologies, breakthroughs in understanding the genetic underpinnings of health and ill health, improvements in the effectiveness and variety of pharmaceuticals, and other developments in biomedical research have helped develop cures for many illnesses and improve the lives of those with chronic diseases. By itself, however, biomedical research cannot address the most significant challenges to improving public health. Approximately half of all causes of mortality in the United States are linked to social and behavioral factors such as smoking, diet, alcohol use, sedentary lifestyle, and accidents. Yet less than five percent of the money spent annually on U.S. health care is devoted to reducing the risks of these preventable conditions. Behavioral and social interventions offer great promise, but as yet their potential has been relatively poorly tapped. Promoting Health identifies those promising areas of social science and behavioral research that may address public health needs. It includes 12 papers—commissioned from some of the nation's leading experts—that review these issues in detail, and serves to assess whether the knowledge base of social and behavioral interventions has been useful, or could be useful, in the development of broader public health interventions.
Keywords: Health and Medicine

Leading Health Indicators for Healthy People 2010: Final Report - Institute of Medicine (The National Academies Press, 1999)
Healthy People is the nation's agenda for health promotion and disease prevention. The concept, first established in 1979 in a report prepared by the Office of the Surgeon General, has since been revised on a regular basis, and the fourth iteration, known as Healthy People 2010 will take the nation into the 21st century. Leading Health Indicators for Healthy People 2010: Final Report contains a number of recommendations and suggestions for the Department of Health and Human Services that address issues relevant to the composition of leading health indicator sets, data collection, data analysis, effective dissemination strategies, health disparities, and application of the indicators across multiple jurisdictional levels.
Keywords: Health and Medicine

Innovations in Design and Utilization of Measurement Systems to Promote Children's Cognitive, Affective, and Behavioral Health: Workshop Summary - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Many measurement systems to monitor the well-being of children and guide services are implemented across the community, state, and national levels in the United States. While great progress has been made in recent years in developing interventions that have been shown to improve the cognitive, affective, and behavioral health of children, many of these tested and effective interventions have yet to be widely implemented. One potential reason for this lag in implementation is a need to further develop and better utilize measures that gauge the success of evidence-based programs as part of a broad effort to prevent negative outcomes and foster children's health and well-being. To address this issue, the Institute of Medicine Forum on Promoting Children's Cognitive, Affective, and Behavioral Health held a workshop in Washington, DC, on November 5-6, 2014. The workshop featured presentations on the use of data linkage and integration to inform research and practice related to children's cognitive, affective, and behavioral health; the use of quality measures to facilitate system change in health care, classroom, and juvenile justice settings; and tools developed to measure implementation of evidence-based prevention programs at scale to support sustainable program delivery, among other topics. Workshop presenters and participants discussed examples of innovative design and utilization of measurement systems, new approaches to build on existing data systems, and new data systems that could support the cognitive, affective, and behavioral health and well-being of children. This report summarizes the presentation and discussions of the event.
Keywords: Health and Medicine

Psychosocial Interventions for Mental and Substance Use Disorders: A Framework for Establishing Evidence-Based Standards - Institute of Medicine (The National Academies Press, 2015)
Mental health and substance use disorders affect approximately 20 percent of Americans and are associated with significant morbidity and mortality. Although a wide range of evidence-based psychosocial interventions are currently in use, most consumers of mental health care find it difficult to know whether they are receiving high-quality care. Although the current evidence base for the effects of psychosocial interventions is sizable, subsequent steps in the process of bringing a psychosocial intervention into routine clinical care are less well defined. Psychosocial Interventions for Mental and Substance Use Disorders details the reasons for the gap between what is known to be effective and current practice and offers recommendations for how best to address this gap by applying a framework that can be used to establish standards for psychosocial interventions. The framework described in Psychosocial Interventions for Mental and Substance Use Disorders can be used to chart a path toward the ultimate goal of improving the outcomes. The framework highlights the need to (1) support research to strengthen the evidence base on the efficacy and effectiveness of psychosocial interventions; (2) based on this evidence, identify the key elements that drive an intervention's effect; (3) conduct systematic reviews to inform clinical guidelines that incorporate these key elements; (4) using the findings of these systematic reviews, develop quality measures - measures of the structure, process, and outcomes of interventions; and (5) establish methods for successfully implementing and sustaining these interventions in regular practice including the training of providers of these interventions. The recommendations offered in this report are intended to assist policy makers, health care organizations, and payers that are organizing and overseeing the provision of care for mental health and substance use disorders while navigating a new health care landscape. The recommendations also target providers, professional societies, funding agencies, consumers, and researchers, all of whom have a stake in ensuring that evidence-based, high-quality care is provided to individuals receiving mental health and substance use services.
Keywords: Health and Medicine

Preventing Psychological Disorders in Service Members and Their Families: An Assessment of Programs - Institute of Medicine (The National Academies Press, 2014)
Being deployed to a war zone can result in numerous adverse psychological health conditions. It is well documented in the literature that there are high rates of psychological disorders among military personnel serving in Operation Enduring Freedom in Afghanistan and Operation Iraqi Freedom in Iraq as well as among the service members' families. For service members' families, the degree of hardship and negative consequences rises with the amount of the service members' exposure to traumatic or life-altering experiences. Adult and child members of the families of service members who experience wartime deployments have been found to be at increased risk for symptoms of psychological disorders and to be more likely to use mental health services. In an effort to provide early recognition and early intervention that meet the psychological health needs of service members and their families, DOD currently screens for many of these conditions at numerous points during the military life cycle, and it is implementing structural interventions that support the improved integration of military line personnel, non-medical caregivers, and clinicians, such as RESPECT-Mil (Re-engineering Systems of Primary Care Treatment in the Military), embedded mental health providers, and the Patient-Centered Medical Home. Preventing Psychological Disorders in Service Members and Their Families evaluates risk and protective factors in military and family populations and suggests that prevention strategies are needed at multiple levels - individual, interpersonal, institutional, community, and societal - in order to address the influence that these factors have on psychological health. This report reviews and critiques reintegration programs and prevention strategies for PTSD, depression, recovery support, and prevention of substance abuse, suicide, and interpersonal violence.
Keywords: Health and Medicine

Paying Attention to Children in a Changing Health Care System (The National Academies Press, 1996)
America's health care system is being reshaped by a variety of market-driven changes, and states are emerging as the major governmental influence on health care policy. Amid these changes, the health and well-being of children can slip from view. Although most children are fundamentally healthy, they require health care that emphasizes preventive services, such as immunizations and regular monitoring of physical and psychosocial growth and development. This volume takes a broad look at access and quality of care for pregnant women, children, and mothers. Among the issues addressed are the scope of benefits available under various health care reform efforts and services for special-needs children under managed care.
Keywords: Health and Medicine